Pengaruh Metode Pembelajaran Means-Ends Analysis (MEA) terhadap Hasil Belajar Matematika - Antik Hikmah Susanti; Suheny Witarti (EduResearch Mitra Inovasi, 2020)
The purpose of the study was to determine the effect of teaching methods Means-Ends Analysis (MEA) on the results of students' mathematics learning class VII Uswatun Hasanah Jakarta. The method used in this study is an experimental method, sampling technique using simple random sampling technique. Instruments to collect data on research in the form of a multiple choice test consisting of 25 items. Calculation of hypothesis testing by t-test at significance level α = 0.05 df = 38 obtained of 2.03 and of 4.40. Because it can be concluded that accepted and rejected, so it can be concluded that the average results of students 'mathematics learning by teaching methods Means-Ends Analysis (MEA) is higher than the average results of students' mathematics learning by learning methods expository. Thus, the learning method Means-Ends Analysis (MEA) influence on mathematics learning outcomes.